Formulation and Antibacterial Activity of Basil (Ocimum basilicum Linn.) Essential Oil Emulgel - Nilmawati, Nilmawati; Novitasari, Putri Rachma; Nuraisyah, Fatma; Rusdi, Niswa Fadilah; Widiyastuti, Lina (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Basil (Ocimum basilicum Linn.) essential oil contains methyl chavicol, which exhibits antibacterial properties. Basil essential oil has volatile and hydrophobic properties, so it is necessary to have an emulgel preparation that can stabilize and enhance its topical activity. This study aims to formulate an emulgel of basil essential oil and investigate its antibacterial activity against Staphylococcus aureus. Basil essential oil was analyzed using the GC-MS. The formulas of Basil essential oil emulgel were created through concentration variations of 5%, 7.5%, and 10%, respectively. These formulas were then tested for organoleptic properties, viscosity, pH, spreadability, and adhesion time. Additionally, antibacterial activity tests were conducted using the well diffusion method. Basil essential oil analysis identified methyl chavicol at 81.34%. All formulas had the white semi-solid form and they had specific basil odours, viscosity 1013.83 ±714.29; 1644.68 ± 888.68; 1923.26 ± 1733.67 cps, pH 5.73; 6.02; 6.90, spreadability 19.61 ± 0.24; 18.28 ± 0.32; 17.57 ± 0.26 gram.cm/second and adhesion time 8.03 ± 1.85; 5.07 ± 0.43; 5.51 ± 0.14 second. Furthermore, all the formulas inhibited the growth of Staphylococcus aureus (p<0.05). The 7.5% basil essential oil emulgel’s formula provides optimal results in terms of physical stability and antibacterial activity.